World Business Cycle, Local Specialization and Asset Prices - Duport, Noëlle; Goyeau, Daniel; Sarte, Genelyn Ma. F. (Philippine Management Review, 2011)
This paper analyzes the contribution of the Southeast and Central Asian countries in international portfolio diversification.  We characterize the stock cycles of six (6) Asian emerging countries (Korea, Malaysia, Philippines, Singapore, Indonesia and Thailand) by comparing their real cycles with the real and financial cycles of the US. The different phases of the cycles are identified using the Markov-switching autoregressive (MSAR) modeling procedure. The synchronization is then measured by the degree of concordance measure of Harding and Pagan (2002). The main result is that three groups of countries can be distinguished: (1) Indonesia, Philippines and Singapore where the financial markets do not depend on the local real conditions but which depend on the American financial market; (2) Korea and Malaysia which are not dependent on the local real conditions, and the US financial market and real conditions; and (3) Thailand unlike other countries does not present a link with its real economy while presenting a link with the US financial market and real US economy but in s countercyclical manner.
Keywords: stock cycle; real cycle; international portfolio diversification